Strategic School Leadership in Religiously Based Teacher Development - zubaidi zubaidi; Romlah Romlah; Amiruddin Amiruddin (JIEM (Journal of Islamic Education Management), 2025)
Teachers are the most important element in the world of education and are inseparable from the transformation of knowledge. Permata Bunda I and II Integrated Islamic Elementary Schools have teachers and educators with diverse educational backgrounds. Some teachers graduated from religious-based universities, while others graduated from public universities. Permata Bunda I and II Integrated Islamic Elementary Schools in Bandar Lampung have a vision and mission, one of which is religious character. It is important for teachers and educators to have religious character. In this study, the author wants to understand the role of the principal in managing human resources, namely teachers and educators, so that each individual teacher and educator has a religious character that is very important in the learning process. The method used in this study is descriptive qualitative, with data collection techniques carried out through observation, interviews, and documentation at Permata Bunda I and II Integrated Islamic Elementary Schools, Bandar Lampung, involving the principal, vice principal, administration department and teachers who are considered able to provide information. The novelty of this study is the religious character development implemented by the principal of Permata Bunda I and II Integrated Islamic Elementary Schools in Bandar Lampung as a consequence of fulfilling the educational institution's vision and mission. Efforts to increase individual teacher capacity include memorization, improvements in Quranic recitation rules, and daily sunnah practices.